EFFECT OF YOGIC EXERCISES ON PERFORMANCE IN CRICKETERS (International Journal of Food and Nutritional Sciences, 2022)
The purpose of the study was to find out the effects of yoga practice and physical exercise on performance among cricket players. The 48 subjects that were chosen were split into three equal groups, each with sixteen members: Group I was designated as a yoga practice group, Group II as a physical exercise group, and Group III as the control group. Subjects in Group I practiced yoga, subjects in Group II engaged in physical exercises, while subjects in Group III engaged in their daily routine rather than any particular yoga or physical activity. The instruction consisted of physical activities and yogic practice. Hence, Yogic practice performs better results interms of confidence level, mean square and capability.